Effects of nutritional supplementation and home visiting on growth and development in young children in Madagascar: a cluster-randomised controlled trial - Emanuela Galasso, PhD; Ann M Weber, PhD; Christine P Stewart, PhD; Lisy Ratsifandrihamanana, MD; Lia C H Fernald (Elsevier, 2019)
Summary: Background: Evidence from efficacy trials suggests that lipid-based nutrient supplementation (LNS) and home visits can be effective approaches to preventing chronic malnutrition and promoting child development in low-income settings. We tested the integration of these approaches within an existing, large-scale, community-based nutrition programme in Madagascar. Methods: We randomly allocated 125 programme sites to five intervention groups: standard-of-care programme with monthly growth monitoring and nutrition education (T0); T0 plus home visits for intensive nutrition counselling through an added community worker (T1); T1 plus LNS for children aged 6-18 months (T2); T2 plus LNS for pregnant or lactating women (T3); or T1 plus fortnightly home visits to promote and encourage early stimulation (T4). Pregnant women (second or third trimester) and infants younger than 12 months were enrolled in the trial. Primary outcomes were child growth (length-for-age and weight-for-length Z scores) and development at age 18-30 months. Analyses were by intention to treat. The trial was registered with the ISRCTN registry, number ISRCTN14393738. Findings: The study enrolled 3738 mothers: 1248 pregnant women (250 women in each of the T0, T1, T2, and T4 intervention groups and 248 in the T3 intervention group) and 2490 children aged 0-11 months (497 children in T0, 500 in T1, 494 in T2, 499 in T3, and 500 in T4) at baseline who were assessed at 1-year and 2-year intervals. There were no main effects of any of the intervention groups on any measure of anthropometry or any of the child development outcomes in the full sample. However, compared with children in the T0 intervention group, the youngest children (<6 months at baseline) in the T2 and T3 intervention groups who were fully exposed to the child LNS dose had higher length-for-age Z scores (a significant effect of 0·210 SD [95% CI −0·004 to 0·424] for T2 and a borderline effect of 0·216 SD [0·043 to 0·389] for T3) and lower stunting prevalence (−9·0% [95% CI −16·7 to −1·2] for T2 and −8·2% [−15·6 to −0·7] for T3); supplementing mothers conferred no additional benefit. Interpretation: LNS for children for a duration of 12 months only benefited growth when it began at an early age, suggesting the need to supplement infants at age 6 months in a very low-income context. The lack of effect of the early stimulation messages and home visits might be due to little take-up of behaviour-change messages and delivery challenges facing community health workers. Funding: Eunice Kennedy Shriver National Institutes of Child Health and Human Development, Strategic Impact Evaluation Fund, World Bank Innovation Grant, Early Learning Partnership Grant, World Bank Research Budget, Japan Nutrition Trust Fund, Power of Nutrition, and the National Nutrition Office of Madagascar.